2017
DOI: 10.1177/1043659617696974
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of Older Italian Migrants With Type 2 Diabetes: A Qualitative Study

Abstract: A need for greater access to interpreters and information in Italian was identified. Counselling services may be necessary for this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Second, living with T2DM and UI involves a challenging self-care regimen for home-care recipients. This finding is consistent with the qualitative literature regarding self-management of T2DM for older adults (Carolan-Olah & Cassar, 2018;Joo & Lee, 2016;Song et al, 2009). The careful balancing that participants described in managing their chronic conditions is commonly reported in the multiple chronic conditions literature (Boyd & Fortin, 2010) For example, that treatment for one condition (e.g., diuresis) worsens another condition (e.g., incontinence), or a treatment (e.g., exercise for weight loss in a person with diabetes) is not feasible due to complications related to another condition (e.g., shortness of breath in chronic obstructive lung disease (Boyd & Fortin, 2010;Grembowski et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Second, living with T2DM and UI involves a challenging self-care regimen for home-care recipients. This finding is consistent with the qualitative literature regarding self-management of T2DM for older adults (Carolan-Olah & Cassar, 2018;Joo & Lee, 2016;Song et al, 2009). The careful balancing that participants described in managing their chronic conditions is commonly reported in the multiple chronic conditions literature (Boyd & Fortin, 2010) For example, that treatment for one condition (e.g., diuresis) worsens another condition (e.g., incontinence), or a treatment (e.g., exercise for weight loss in a person with diabetes) is not feasible due to complications related to another condition (e.g., shortness of breath in chronic obstructive lung disease (Boyd & Fortin, 2010;Grembowski et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Some qualitative descriptive research has explored the experiences of living with diabetes for older adults. These participants experienced challenges in self-managing, such as forgetting to take medications or feeling too unwell to exercise (Carolan-Olah & Cassar, 2018; Joo & Lee, 2016; Song et al, 2009). Older adults described benefiting from assistance with self-management activities, such as meal preparation, from caregivers and home-care providers (Brewer-Lowry et al, 2010; Song et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, one study[ 31 ] reported that some participants received benefits when they understood the information; they were motivated to continue their self-management behaviors when they knew the benefits of self-management. They sought information initiatives[ 32 ] and were happier to learn more about diabetes care[ 33 ]. This theme shows high confidence according to the CERQual assessment and details are presented in Table 3 below.…”
Section: Resultsmentioning
confidence: 99%
“…Seven of ten papers mentioned functional decline[ 27 , 30 - 33 , 36 , 37 ], discussing aging-related symptoms, memory loss, joint pain, deterioration of vision, peripheral nerve damage, and weakness, which made self-management challenging for the participants. Owing to memory loss, the participants sometimes forgot to take their prescribed medicines, or were unable to remember whether or not they had taken their prescribed medicines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation